Kunstenaars die met kunstlicht werken. - Van Abbemuseum, Eindhoven; s.n. (Eindhoven : Van Abbemuseum Eindhoven, 1979)
Riverhead (New York) ; Morellet, François ; Sonnier, Keith ; Zorio, Gilberto ; Merz, Mario ; Dibbets, Jan ; Anselmo, Giovanni ; van Munster, Jan ; Flanagan, Barry ; Nauman, Bruce ; Kosuth, Joseph ; Salvo ; van Bakel, Gerrit
geboortedata per kunstenaar
Nederlands
Kunstenaars die met kunstlicht werken, Van Abbemuseum Eindhoven, 19.4 tm 13.5.1979
boek